Successful Rescue of an Adult With Refractory Anaphylactic Shock and Abdominal Compartment Syndrome With Venoarterial Extracorporeal Membrane Oxygenation and Bedside Laparotomy. (March 2015) - Weiss, Gregory Michael; Fandrick, Ashley D.; Sidebotham, David
The incidence of life-threatening anaphylactic reactions related to anesthesia is approximately 1 in 6000 anesthetics administered, and is associated with mortality as high as 5%. In such cases the use of extracorporeal membrane oxygenation (ECMO) in the setting of refractory shock following anaphylaxis may be life saving. Abdominal compartment syndrome (ACS) itself and in this case complicating ECMO support, is a potentially devastating complication of high-volume resuscitation. Decompressive laparotomy is the treatment of choice for ACS. We present a patient treated with venoarterial ECMO for refractory shock following anaphylaxis who developed ACS that was successfully treated with urgent decompressive laparotomy performed in the intensive care unit. This case report highlights the role of abdominal compartment syndrome as a rare but potentially fatal cause of low circuit flow in ECMO-supported patients and proposes a stepwise approach to decision making in this setting. Urgent decompressive laparotomy is potentially lifesaving in this circumstance, and should be urgently considered once other causes of low ECMO flow have been excluded.